Evaluation of the effect of iodine substitution of 8-hydroxyquinoline on its platinum(ii) complex: cytotoxicity, cell apoptosis and telomerase inhibition12. Issue 9 (21st July 2016) - Meng, Ting; Tang, Shang-Feng; Qin, Qi-Pin; Liang, Yue-Lan; Wu, Chen-Xuan; Wang, Chen-Yu; Yan, Hou-Tian; Dong, Jia-Xin; Liu, Yan-Cheng
Abstract : A new Pt(ii ) complex of 5, 7-diiodo-8-quinolinol was synthesized and studied on its more effective antitumor mechanism than that of 8-quinolinol. Abstract : Two platinum(ii) complexes, [PtCl(Q)(DMSO)] (1 ) and [PtCl(IQ)(DMSO)] (2 ), bearing 8-hydroxyquinoline (H-Q) and 5, 7-diiodo-8-hydroxyquinoline (H-IQ) as the bioactive ligand, respectively, were synthesized and structurally characterized. By MTT assay, complex2 bearing the IQ ligand showed significantly higher growth inhibition than complex1 against all the five typical tumor cell lines in the test, but showed no more cytotoxicity against the normal liver cell line HL-7702, suggesting the much better cytotoxic selectivity of2 than that of1 . In addition, the HepG2 cell line was found to be the most sensitive towards both complexes. Aiming at the HepG2 cell line, both complexes arrested the cell cycle of HepG2 cells in the S phase, as examined by flow cytometry, in which complex2 showed higher S-phase arrest than1 . This was supported by the down-regulation of cdc25 A, cyclin B, cyclin A, and CDK2 and the up-regulation of p53, p27 and p21 based on western blot assay. Complex2 also acted as a more effective telomerase inhibitor than1 by interacting with telomeric/c-myc G-quadruplexes and triggering cell senescence and cell apoptosis. Furthermore, both complexes caused mitochondrial dysfunction, suggesting a potential mitochondrion-mediated apoptotic pathway induced by each complex. From the platinum uptake assay, complex2 exhibited obvious priority on the cell uptake effect than1, which should be undoubtedly correlated with the key roles of the 5- and 7-iodo-substituted groups in the IQ ligand of2 . This may well explain the better cytotoxicity and the more significant antitumor mechanism of2 throughout the study. This work further demonstrated that rational halogen substitution on selected ligands would be greatly beneficial to achieve more promising metal-based antitumor agents.